2011
DOI: 10.1042/bst0390213
|View full text |Cite
|
Sign up to set email alerts
|

Nitrosative stress in Escherichia coli: reduction of nitric oxide

Abstract: The ability of enteric bacteria to protect themselves against reactive nitrogen species generated by their own metabolism, or as part of the innate immune response, is critical to their survival. One important defence mechanism is their ability to reduce NO (nitric oxide) to harmless products. The highest rates of NO reduction by Escherichia coli K-12 were detected after anaerobic growth in the presence of nitrate. Four proteins have been implicated as catalysts of NO reduction: the cytoplasmic sirohaem-contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
45
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 19 publications
(15 reference statements)
1
45
0
Order By: Relevance
“…2A). By contrast, a small contribution (<3%) from the periplasmatic Nap to NO formation has been reported in both bacteria (Gilberthorpe & Poole, 2008;Rowley et al, 2012;Vine & Cole, 2011).…”
Section: Enzymes Involved In No and N 2 O Metabolismmentioning
confidence: 96%
“…2A). By contrast, a small contribution (<3%) from the periplasmatic Nap to NO formation has been reported in both bacteria (Gilberthorpe & Poole, 2008;Rowley et al, 2012;Vine & Cole, 2011).…”
Section: Enzymes Involved In No and N 2 O Metabolismmentioning
confidence: 96%
“…However, this reduction capacity is low compared with that of NorVW or NrfA. The alternative view is therefore that FNR represses transcription of hmp under anaerobic conditions so that alternative, more effective, protection mechanisms are activated anaerobically (Vine & Cole, 2011a). It is possible, however, that Hmp synthesis becomes physiologically relevant under extreme environmental conditions.…”
Section: Repair Of Nitrosative Damagementioning
confidence: 99%
“…Although the importance of these reactive nitrogen and oxygen intermediate species has been documented for host defense reactions against bacteria and fungi, their role in the pathogenesis of viral infections is only partly understood [9,10]. It has been reported that nitric oxide (NO) has deleterious consequences in the presence of reactive oxygen species, since peroxynitrites are formed.…”
Section: Introductionmentioning
confidence: 99%